2021
DOI: 10.32604/or.2022.025323
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT signaling pathway as a critical regulator of Cisplatin response in tumor cells

Abstract: Chemotherapy is one of the main therapeutic modalities for cancer patients. Cisplatin (CDDP), as one of the first-line drugs, is of great importance in the chemotherapy of various tumors. However, a significant percentage of cancer patients are resistant to CDDP treatment. Due to the CDDP side effects on normal tissues, the diagnosis of CDDP resistance is required to suggest the most efficient therapeutic strategies for cancer patients. Several molecular mechanisms and signaling pathways are associated with CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 176 publications
0
19
0
Order By: Relevance
“…Considering miR-17-5p and STAT3 pathway are closely associated with chemoresistance of cancer cells (Chatterjee et al, 2014;Jiang et al, 2014;Laurino et al, 2023;Ma et al, 2023;Sun et al, 2019;Yang et al, 2023;Wang & Ji, 2018), and in this study we observe that β-elemene upregulates the expression of miR-17-5p and represses the expression of STAT3, we conclude that β-elemene sensitizes NSCLC cells to cisplatin via modulating miR-17-5p/STAT3 axis, and this is a different mechanism compared with the previous report (Yao et al, 2014). It should be emphasized, cancer cells' resistance to Platinum chemotherapeutic drugs is caused by multiple mechanisms, and modulated by various signal pathways, such as the activation of PI3K/Akt pathway, pentose phosphate pathway, abnormal epigenetic modifications et al (Giacomini et al, 2020;Navaei et al, 2022;Zhang et al, 2014). The other mechanisms by which β-elemene sensitizes NSCLC cells to chemotherapeutics are far from being fully clarified.…”
Section: On Nsclc Cells Is Partially Reversed By Stat3 Overexpressionmentioning
confidence: 59%
See 1 more Smart Citation
“…Considering miR-17-5p and STAT3 pathway are closely associated with chemoresistance of cancer cells (Chatterjee et al, 2014;Jiang et al, 2014;Laurino et al, 2023;Ma et al, 2023;Sun et al, 2019;Yang et al, 2023;Wang & Ji, 2018), and in this study we observe that β-elemene upregulates the expression of miR-17-5p and represses the expression of STAT3, we conclude that β-elemene sensitizes NSCLC cells to cisplatin via modulating miR-17-5p/STAT3 axis, and this is a different mechanism compared with the previous report (Yao et al, 2014). It should be emphasized, cancer cells' resistance to Platinum chemotherapeutic drugs is caused by multiple mechanisms, and modulated by various signal pathways, such as the activation of PI3K/Akt pathway, pentose phosphate pathway, abnormal epigenetic modifications et al (Giacomini et al, 2020;Navaei et al, 2022;Zhang et al, 2014). The other mechanisms by which β-elemene sensitizes NSCLC cells to chemotherapeutics are far from being fully clarified.…”
Section: On Nsclc Cells Is Partially Reversed By Stat3 Overexpressionmentioning
confidence: 59%
“…It should be emphasized, cancer cells' resistance to Platinum chemotherapeutic drugs is caused by multiple mechanisms, and modulated by various signal pathways, such as the activation of PI3K/Akt pathway, pentose phosphate pathway, abnormal epigenetic modifications et al. (Giacomini et al., 2020; Navaei et al., 2022; Zhang et al., 2014). The other mechanisms by which β‐elemene sensitizes NSCLC cells to chemotherapeutics are far from being fully clarified.…”
Section: Discussionmentioning
confidence: 99%
“…1 C). which are involved in the regulation of cisplatin resistance in various tumors [ [24] , [25] , [26] ]. Subsequently, GSEA was performed to evaluate the enriched gene signatures related to canonical signaling pathways in cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The development of cisplatin resistance results from the interaction of multiple complex factors involving the regulation of several cellular signaling pathways. In recent years, increasing evidence [19][20][21] has shown that the PI3K/AKT/MAPK3 pathway plays a crucial role in cisplatin resistance and that its aberrant activation is closely related to the resistance phenomenon. The PI3K/AKT/ MAPK signaling pathway is an important cell signaling pathway involved in the regulation of life activities such as cell survival, proliferation, differentiation, and apoptosis [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The AKT signaling pathway plays a key role in cell survival, proliferation, and drug resistance. The high expression of KIF2C may lead to the overactivation of the PI3K/ AKT pathway, enhance cell survival signaling, and reduce cell apoptosis in response to cisplatin-induced apoptosis [20]. In addition, KIF2C overexpression may promote the activation of the MAPK3 signaling pathway by interacting with MAPK3, which is involved in cell proliferation, differentiation, and survival and is closely related to tumorigenesis and drug resistance.…”
Section: Discussionmentioning
confidence: 99%